THE ROYAL COMITÉ LIÉGEOIS DE VOLLEY-BALL OF BELGIUM (Fiep Bulletin - online, 2014)
This text describes the experience developed during the interchange between the Doctorate in Education Program from PUC-GO and the Service Intervention et Gestion en Activité Physiques et Sportives du Département des Sciences de la Motricité de la Université de Liège, in Liège, Belgium, in the area of volleyball. The purpose was to describe the organization and the activities provided specially in volleyball within the Pólo Liégeois of Development. It was concluded that sport/volleyball In Belgium is available with quality for a great part of the population interested in learning ang playing it, being inclusive and contemplative for different age groups and levels of learning.
Keywords: Sports; Volleyball; Organization; Liège / BE.